Developing a TPaCK Textbook to Support the ScaPro-PjBL Model: Preparing Pre-Service Physics Teacher Competencies in Distance Learning for SDG 4 - Gaguk Resbiantoro; Wasis Wasis; Wahono Widodo (Journal of Current Studies in SDGs, 2026)
Objective: This study evaluates the validity and practicality of a TPaCK textbook as supporting teaching material for the Scaffolded Product in Project-Based Learning (ScaPro-PjBL) model for training pre-service physics teachers in TPaCK. It focuses on three phases: starting with essential questions, designing a project with a timeline and checkpoints, and providing tutorials on subject-specific techniques and methods. Method: The textbook development followed Plomp’s stages of preliminary research, development/prototyping, and assessment. The textbook has five chapters on the TPaCK concept, framework, application in physics distance learning, supporting technology, and TPaCK products. Validity was assessed by three experts using the Indonesian National Agency of Education Standards (NAES) criteria for content, presentation, language, and graphics, with scores ranging from 1 to 10. Reliability was calculated using ICC(3,k) and Cronbach's Alpha. Practicality was tested through limited (21 students) and extensive (98 students) trials using questionnaires 1–4, with similar reliability analyses. Results: The TPaCK textbook is valid and practical, and it supports students in understanding concepts, designing TPaCK-based learning products, determining project needs, following technical tutorials, and developing products such as online lesson plans, digital worksheets, video materials, and application-based formative evaluations. Conceptual scaffolding supports the initial phase, while procedural scaffolding guides mastery of technology. Multimodal presentation and accessibility enhance ease of use. Novelty: This textbook is designed as scaffolding for ScaPro-PjBL implementation in preparing pre-service physics teachers for distance learning. It serves as content support, a practice guide, a conceptual mediator, and a procedural tool for developing TPaCK.